Relationship of Environmental Conditions with the Development of Viral Diseases on Two Genotypes of Potato - and S.K. Singh, Rajesh Kumar*, L.P. Awasthi, N.K. Sharma (Journal of Phytology, 2011)
Two genotypes viz. Kufri Ashoka and Kufri Chipsona-1 were selected to study the relationship of environmental conditions (maximum and minimum temperature, relative humidity and rainfall) with viral disease(s) of potato. Maximum disease intensity (80.5, 82.70% and 10.20,12.45%) was recorded in fourth week of January during 2008-09 and 2009-10 in Kufri Ashoka and Kufri Chipsona-1, respectively. Disease was favoured by minimum temperature from 7.3 to 10.3 0C and maximum temperature 27.1 to 23.3 0C along with minimum relative humidity 53.80 to 51.20% and maximum relative humidity 93.6 to 92.7% during 2008-09, while in the year 2009-10 minimum temperature ranged 4.8 to 7.6 0C, maximum temperature 23.42 to 17.0 0C along with minimum relative humidity 45.85 to 71.57% and maximum relative humidity from 87.71 to 90.71%, respectively, during the period of maximum disease development.